Evaluation of sodium alginate for bone marrow cell tissue engineering. - Wang, L; Shelton, R; Cooper, P; Lawson, M; Triffitt, J; Barralet, J (2003)
Sodium alginate has applications as a material for the encapsulation and immobilisation of a variety of cell types for immunoisolatory and biochemical processing applications. It forms a biodegradable gel when crosslinked with calcium ions and it has been exploited in cartilage tissue engineering since chondrocytes do not dedifferentiate when immobilised in it. Despite its attractive properties of degradability, ease of processing and cell immobilisation, there is little work demonstrating the efficacy of alginate gel as a substrate for cell proliferation, except when RGD is modified. In this study we investigated the ability of rat bone marrow cells to proliferate and differentiate on alginates of differing composition and purity. The mechanical properties of the gels were investigated. It was found that high purity and high G-type alginate retained 27% of its initial strength after 12 days in culture and that comparable levels of proliferation were observed on this material and tissue culture plastic. Depending on composition, calcium crosslinked alginate can act as a substrate for rat marrow cell proliferation and has potential for use as 3D degradable scaffold.